Using two-way coupled DEM-SPH to model an industrial scale Stirred Media Detritor. (15th June 2019) - Ndimande, C.B.; Cleary, P.W.; Mainza, A.N.; Sinnott, M.D.
Highlights: Two-way DEM+SPH is used to simulate operational behaviour of an industrial SMD. The model provides detail of the particle-particle and particle-fluid interactions. The central vortex with charge recirculation in an SMD is modelled. The significant effects of the slurry on charge dynamics are captured by DEM+SPH. DEM only simulation has higher media-media dissipation and lower mill power draw. Abstract: The Stirred Media Detritor (SMD) is one of the milling devices used in concentrators for fine and ultra-fine grinding applications. The SMD has a vertically orientated octagonal shell which supports a vertical shaft that has protruding impeller arms to agitate the charge. There is very little understanding of the motion and physical structure of the charge during operation in these devices. This paper explores the flow and interaction of media and slurry in a commercially available SMD 1100E, which has a motor with a power rating of 1100 kW. A transient two-way coupled Discrete Element Method (DEM) and Smoothed Particle Hydrodynamics (SPH) model is used to achieve this. The DEM component represents the ceramic grinding media which is fully resolved while the SPH model represents the slurry (water and fine feed and/or product). The centrifugal force generated by the rotational action of the impeller arms pushes the charge to the mill wall creating a vortex. The agitator also produces a pumping like effect which drives the charge upwards. The media was found to pack tightly with solid fractions of around 0.5 which decreases to around 0.16 in the thin mobile surface layers of the charge on the inside of the vortex. Radial motion of the charge is restricted to a thin surface layer with the slurry demonstrating higher mobility than the media. The tangential velocity for both the media and the slurry is zero at and near the mill wall and increases towards the free surface of the vortex. For the conditions tested, the mill power draw was 985.7 kW which is ∼90% of installed power, of which 66% is dissipated in media interactions while 34% is dissipated by viscous stresses in the slurry. Abrasion is found to be the dominant breakage mechanism in the SMD. The importance of including the slurry phase in the modelling is quantified.